Impacto familiar de niños y jóvenes con Autismo de la “Asociación de Padres de personas con autismo- Loja” - Rodríguez Gálvez, Angie Nicole (2022)
Impact is considered a fact that transcends generating a change; the autism spectrum disorder (ASD) is a neurodevelopmental condition with difficulties in social and behavioral language, children with autism have a relevant impact on family dynamics, causing undoubtedly changes. The present research aimed to determine the family impact of children and young people diagnosed with autism of the "Asociación de Padres de Personas con Autismo Loja" during the period April 2020 and March 2021; to obtain sociodemographic information and to know the impact that families of a person with autism have; two questionnaires were applied: one about the family impact and the other about sociodemographic information, in a virtual way. The results obtained showed that the majority of members belong to the female sex with 79.41%, with an age range of 35 to 40 years 29.41%, 58.82% are married, with a higher level of education in 91.17%, 82.35% conform nuclear families, 97.05% refer that their income is higher than a unified basic remuneration and 8. In light of these results, it is of vital importance that the parents of these children have support that allows them to learn new strategies to cope with the behavioral and educational problems of their children